Bringing Fishermen Together Through the Customary Maritim Law of the Sea in the South West Aceh Region: al-Shulh's Perspective - Baddah, Laylay Alfaytouri; Yusuf, Muhammad; Humaira, Humaira; Qatrunnada SM, Sy Alyssa; Khumaira, Siti (Faculty of Sharia and Law, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
Panglima Laot is a customary structure among fishing communities in Aceh province, which is tasked with leading the customary alliance managing Laot customary law. Panglima Laot resolves marine disputes using the principles of harmony, harmony, and appropriateness. Thus, there are three problem formulations in this paper. First, what are the forms of minor criminal offenses that occur in the Marine Area of Susoh Sub-district, Southwest Aceh Regency? Second, how is the process of resolving minor crimes between fishermen in the sea area of Susoh District, Southwest Aceh Regency by Panglima Laot? Third, how is the settlement of minor crimes in the sea area of Susoh District, Southwest Aceh Regency, according to Ṣulḥu? This research is field research and uses a qualitative approach. That is by interviewing the Panglima Laot of Southwest Aceh. The results showed that. First, there are three cases of minor crimes that occurred in the sea of Susoh District, Southwest Aceh Regency, including cases of fighting, cases of bloodshed fights, and cases of fish theft. Second, the process of resolving these minor crimes is carried out by first making a report to the Panglima Laot Teupin, then the Panglima Laot te also makes a report to the Panglima Laot Lhok and the district Panglima Laot, and a customary hearing is made which is attended by members of the Panglima Laot along with village officials and the families concerned then the disputing parties get advice from the Panglima Laot and village officials who are present to make peace, finally giving fines outside the trial. Third, the settlement of minor crimes at sea in Susoh District, Southwest Aceh Regency is in accordance with the concept of al-Ṣulḥu, namely settlement by deliberation and fairness.